2015
DOI: 10.1186/s12884-015-0558-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy intendedness and the association with physical, sexual and emotional abuse – a European multi-country cross-sectional study

Abstract: BackgroundUnintended pregnancies are common and when not resulting in a termination of pregnancy may lead to unintended childbirth. Unintended pregnancies are associated with increased health risks, also for women for whom pregnancy continues to childbirth. Our objective was to present the prevalence of unintended pregnancy in six European countries among pregnant women attending routine antenatal care, and to investigate the association with a history of physical, sexual and emotional abuse.MethodsA prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 37 publications
4
50
1
1
Order By: Relevance
“…For example, the proportion of IPIs greater than or equal to 24 months is higher in our study compared to a recent population‐based Norwegian study using data from 2006 to 2014 (60% vs 37%, respectively), and we found a slightly longer mean IPI compared to a population‐based study from the United States using data from 2006 to 2010 (34 months vs 37 months, respectively) . In addition, in our cohort, 70% of pregnancies were intended, compared to 49% of pregnancies in the United States in 2008, and 80% of pregnancies in a cross‐sectional European study of women attending routine prenatal care between 2008 and 2010 . These variations may due to the inherent complexity of pregnancy intention which make it difficult to measure .…”
Section: Commentsupporting
confidence: 89%
“…For example, the proportion of IPIs greater than or equal to 24 months is higher in our study compared to a recent population‐based Norwegian study using data from 2006 to 2014 (60% vs 37%, respectively), and we found a slightly longer mean IPI compared to a population‐based study from the United States using data from 2006 to 2010 (34 months vs 37 months, respectively) . In addition, in our cohort, 70% of pregnancies were intended, compared to 49% of pregnancies in the United States in 2008, and 80% of pregnancies in a cross‐sectional European study of women attending routine prenatal care between 2008 and 2010 . These variations may due to the inherent complexity of pregnancy intention which make it difficult to measure .…”
Section: Commentsupporting
confidence: 89%
“…[23] Regarding the health of the child, our material does not allow us to determine to what extent the mothers’ worries mirror low maternal mood, manifest problems in the child due to physiological and epigenetic imprinting, or a subtle mixture of effects, which is a highly plausible interpretation, in view of the most recent evidence. [11,24,25]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, information and awareness 19 about various methods of post-abortion contraception 16 and especially the facilitation of specialized services in women's health should be promoted 9,21 . The benefits of legalizing abortion in Brazil in the cases provided by law 18,20 show a reduction in the number of hospitalizations in public hospitals due to complications of abortion over the years and a reduction in maternal mortality 7,25,26 . This occurs in developed and developing countries especially when associated with a set of measures that guarantee knowledge about legalization in the population.…”
Section: Discussionmentioning
confidence: 99%